Silicon-carbon negative electrode material and preparation method and application thereof
A silicon-carbon negative electrode material with a graphite core and nano-carbon coating addresses adhesion and conductivity issues, enhancing performance and stability in lithium-ion batteries.
Patent Information
- Application Number
- CN202411089086.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-09
- Publication Date
- 2024-12-20
AI Technical Summary
The weak bonding force between silicon and carbon in silicon-carbon negative electrode materials leads to detachment of silicon particles, poor conductivity, and volume change issues, limiting their commercial application in lithium-ion batteries.
A silicon-carbon negative electrode material is prepared by mixing graphite, nano-silicon, and boron oxide, followed by calcination to form a nano-carbon coating, enhancing adhesion and conductivity while buffering volume expansion.
The material achieves high discharge specific capacity and coulombic efficiency, with improved electronic conductivity and stability, resulting in batteries with high initial efficiency, good cycle performance, and safety.
Smart Images

Figure CN119170760A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of battery technology, and in particular to a silicon-carbon negative electrode material and a preparation method and application thereof. Background Art
[0002] The theoretical specific capacity of graphite in the negative electrode of lithium-ion batteries is only 372mAh / g, which is far from meeting the needs of high-energy lithium-ion batteries. Silicon has a high theoretical specific capacity of 4200mAh / g and is considered to be the most promising material to replace graphite negative electrodes. However, silicon has a volume change of up to 300% during the charge and discharge process, which causes it to repeatedly expand and contract during the charge and discharge process, thereby forming a large internal stress inside the material, resulting in the breakage of silicon particles and severe pulverization of the electrode; in addition, the electronic conductivity and ionic conductivity of silicon negative electrodes are both low, which seriously restricts its widespread commercial application. By dispersing silicon active particles in a conductive carbon matrix to form a silicon-carbon composite material, while taking into account the high specific capacity of silicon and the high conductivity of carbon, the carbon material is also conducive to buffering the volume expansion of silicon particles. Therefore, the silicon-carbon composite material is expected to become one of the next generation of lithium-ion battery negative electrode materials for commercial application.
[0003] At present, there are many studies on the structural design of silicon-carbon composite materials, such as core-shell structure, yolk structure, porous structure and embedded structure. These structural designs cannot solve the problems of poor interface adhesion between silicon and carbon matrix and easy electrical contact loss during continuous charging and discharging, and have limited effect on alleviating the volume change of silicon and improving the electrical conductivity of the material.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] One object of the present invention is to provide a silicon-carbon negative electrode material to solve the problem in the prior art that the weak bonding force between the silicon material and the carbon material in the silicon-carbon negative electrode material causes the silicon particles to easily detach from the surface of the carbon material, thereby causing the conductivity of the negative electrode material to deteriorate.
[0006] Another object of the present invention is to provide a method for preparing the silicon-carbon negative electrode material, which is simple and easy to implement and can obtain a silicon-carbon negative electrode material with excellent electrochemical performance.
[0007] Another object of the present invention is to provide a negative electrode sheet.
[0008] Another object of the present invention is to provide a battery.
[0009] Another object of the present invention is to provide an electrical device.
[0010] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0011] A silicon-carbon negative electrode material comprises a substrate and a coating layer coated on the surface of the substrate, wherein the substrate comprises an inner core and a composite layer located on the surface of the inner core; the inner core comprises graphite; the composite layer comprises nano-silicon and boron oxide; and the coating layer comprises nano-carbon.
[0012] In some embodiments, the graphite comprises spherical graphite.
[0013] In some embodiments, the battery prepared from the silicon-carbon negative electrode material has a first discharge specific capacity of more than 440 mAh / g under the test conditions of 25° C., 0.1C, and 0.05-2.5V.
[0014] In some embodiments, the first coulombic efficiency of the battery prepared by the silicon-carbon negative electrode material is 79% or above.
[0015] The method for preparing the silicon-carbon negative electrode material as described above comprises the following steps:
[0016] Graphite, nano-silicon, boron compound and water are first mixed and first calcined to obtain a base material; the base material and a pyrolysis carbon source solution are second mixed and second calcined to obtain a silicon-carbon negative electrode material.
[0017] In some embodiments, the boron compound comprises at least one of boron oxide and boric acid.
[0018] In some embodiments, the pyrolytic carbon source solution includes a pyrolytic carbon source and water, and the mass content of the pyrolytic carbon source in the pyrolytic carbon source solution is 5% to 8%; the pyrolytic carbon source includes a water-soluble carbon source and / or a water-insoluble carbon source.
[0019] In some embodiments, the mass ratio of the nano-silicon to the graphite is x:(1-x), wherein 0 <x≤0.4。
[0020] In some embodiments, the ratio of the mass of the boron element in the boron compound to the total mass of the nano-silicon and the graphite is y:1, wherein 0 <y≤0.1。
[0021] In some embodiments, the mass ratio of the boron compound to the water is 1:(30-40).
[0022] In some embodiments, the mass ratio of the pyrolytic carbon source in the pyrolytic carbon source solution to the matrix material is (2-6):(1-5).
[0023] In some implementations, the first mixing speed is 1500-2000 rpm, and the first mixing time is 20-40 min.
[0024] In some embodiments, the temperature of the first calcination is 300-600° C., and the time of the first calcination is 1-10 hours.
[0025] In some embodiments, the first calcination is performed under protective gas conditions.
[0026] In some embodiments, a first drying step is further included between the first mixing and the first calcining.
[0027] In some embodiments, the first drying temperature is 80 to 120° C., and the first drying time is 24 to 48 hours.
[0028] In some implementations, the method further includes: sequentially performing a first crushing process and a first screening process on the first calcined material.
[0029] In some implementations, the rotation speed of the first crushing process is 200-300 rpm, and the time of the first crushing process is 4-5 hours.
[0030] In some embodiments, the first screening process includes: passing through a 350-mesh sieve.
[0031] In some implementations, the second mixing speed is 1500-2000 rpm, and the second mixing time is 20-40 min.
[0032] In some embodiments, the second calcination temperature is 600-950° C., and the second calcination time is 1-10 hours.
[0033] In some embodiments, the second calcination is performed under protective gas conditions.
[0034] In some embodiments, a second drying step is further included between the second mixing and the second calcining.
[0035] In some embodiments, the second drying temperature is 80 to 120° C., and the second drying time is 24 to 48 hours.
[0036] In some implementations, the method further includes: sequentially performing a second crushing process and a second screening process on the material obtained by the second roasting.
[0037] In some implementations, the second crushing speed is 200-300 rpm, and the second crushing time is 4-5 hours.
[0038] In some embodiments, the second screening process includes: passing through a 350-mesh sieve.
[0039] A negative electrode sheet comprises the silicon-carbon negative electrode material or the silicon-carbon negative electrode material prepared by the method for preparing the silicon-carbon negative electrode material.
[0040] A battery comprises the negative electrode sheet.
[0041] An electrical device comprises the battery.
[0042] Compared with the prior art, the present invention has the following beneficial effects:
[0043] (1) The silicon-carbon negative electrode material of the present invention uses graphite as the core, and the solvent boron oxide uniformly adheres nano-silicon to the graphite surface, which can improve the adhesion between nano-silicon and graphite and prevent the silicon material from falling off the graphite surface during charging and discharging; the nano-carbon coating layer can prevent the silicon particles from directly contacting the electrolyte to cause side reactions, and at the same time increase the electronic conductivity of the silicon-carbon negative electrode material; the silicon-carbon negative electrode material of the present invention has excellent comprehensive electrochemical properties.
[0044] (2) The preparation method of the silicon-carbon negative electrode material of the present invention is simple and easy. The method comprises the following steps: firstly mixing graphite, nano-silicon, a boron compound and water and then performing a first calcination. The liquefaction phenomenon and ductility of the boron compound during low-temperature calcination are utilized to achieve uniform dispersion of nano-silicon on the graphite surface and firm adhesion to the graphite surface, thereby effectively inhibiting the separation and agglomeration of silicon and the graphite matrix during the charge and discharge process. The matrix material is further mixed with a pyrolytic carbon source solution and then performed a second calcination to form a uniform nano-carbon coating layer on the surface of the matrix material. The volume expansion of the silicon particles is buffered while avoiding the occurrence of side reactions caused by direct contact between the silicon particles and the electrolyte, thereby increasing the electronic conductivity of the silicon-carbon negative electrode material.
[0045] (3) The battery prepared by the silicon-carbon negative electrode material of the present invention has high initial efficiency, good cycle performance, rate performance and good safety performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0047] Figure 1 Schematic diagram of the structure of the silicon-carbon negative electrode material of the present invention.
[0048] Reference numerals:
[0049] 1-matrix, 101-core, 102-composite layer, 2-cladding layer. DETAILED DESCRIPTION
[0050] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.
[0051] According to one aspect of the present invention, the present invention relates to a silicon-carbon negative electrode material, comprising a substrate and a coating layer coated on the surface of the substrate, wherein the substrate comprises an inner core and a composite layer located on the surface of the inner core; the inner core comprises graphite; the composite layer comprises nano-silicon and boron oxide; and the coating layer comprises nano-carbon.
[0052] The silicon-carbon negative electrode material of the present invention uses graphite as the core, and the solvent boron oxide uniformly adheres nano-silicon to the graphite surface, which can improve the adhesion between nano-silicon and graphite and prevent the silicon material from falling off the graphite surface during charging and discharging; the nano-carbon coating layer can prevent the silicon particles from directly contacting the electrolyte to cause side reactions, and at the same time increase the electronic conductivity of the silicon-carbon negative electrode material. Therefore, the silicon-carbon negative electrode material of the present invention has excellent comprehensive electrochemical performance.
[0053] In some embodiments, the graphite comprises spherical graphite.
[0054] In some embodiments, the battery prepared from the silicon-carbon negative electrode material has a first discharge specific capacity of more than 440 mAh / g, such as 445 mAh / g, 480 mAh / g, 500 mAh / g, 550 mAh / g, 600 mAh / g, etc., or any range between the two, under the test conditions of 25°C, 0.1C, and 0.05-2.5V.
[0055] In some embodiments, the first coulombic efficiency of the battery prepared with the silicon-carbon negative electrode material is 79% or above, for example, 79%, 80%, 82%, 85%, 88%, 90%, 91%, etc., or any range value between the two.
[0056] According to another aspect of the present invention, the present invention also relates to a method for preparing the silicon-carbon negative electrode material as described above, comprising the following steps:
[0057] The graphite, nano-silicon, boron compound and water are first mixed and first calcined to obtain a matrix material; the matrix material and a pyrolysis carbon source solution are second mixed and second calcined to obtain a silicon-carbon negative electrode material.
[0058] The preparation method of the silicon-carbon negative electrode material of the present invention is simple and easy to implement. By first mixing graphite, nano-silicon, boron compound and water, and then performing first calcination, the liquefaction phenomenon and ductility of the boron compound during low-temperature calcination are utilized to achieve uniform dispersion of nano-silicon on the graphite surface and firmly adhere it to the graphite surface, effectively inhibiting the separation and agglomeration of silicon and the graphite matrix during charge and discharge; further, the matrix material and the pyrolytic carbon source solution are secondarily mixed and secondarily calcined to form a uniform nano-carbon coating layer on the surface of the matrix material, which can avoid side reactions caused by direct contact between silicon particles and the electrolyte while buffering the volume expansion of silicon particles and increasing the electronic conductivity of the silicon-carbon negative electrode material.
[0059] In some embodiments, the boron compound includes at least one of boron oxide and boric acid.
[0060] In some embodiments, the pyrolytic carbon source solution includes a pyrolytic carbon source and water, and the mass content of the pyrolytic carbon source in the pyrolytic carbon source solution is 5% - 8%, such as 5%, 5.5%, 6%, 6.5%, 7%, etc.; the pyrolytic carbon source includes a water-soluble carbon source and / or a water-insoluble carbon source. The water-soluble carbon source includes polyvinylidene fluoride (PVDF). The water-insoluble carbon source includes starch.
[0061] In some embodiments, the mass ratio of nano-silicon to graphite is x:(1 - x), where 0 < x ≤ 0.4. In some embodiments, the value of x includes but is not limited to 0.01, 0.02, 0.05, 0.08, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, etc. In some embodiments, the mass ratio of nano-silicon to graphite is 0.01:0.99, 0.05:0.95, 0.1:0.9, 0.15:0.85, 0.2:0.8, 0.25:75, 0.3:0.7, 0.35:0.65, 0.4:0.6, etc. The appropriate mass ratio of nano-silicon and graphite in the present invention is more conducive to the coordinated action of the two, ensuring the electrochemical performance of the silicon-carbon negative electrode material.
[0062] In some embodiments, the mass ratio of the boron element in the boron compound to the total mass of the nano-silicon and graphite is y:1, where 0 < y ≤ 0.1. In some embodiments, the value of y includes but is not limited to 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, or 0.1, etc., or the range value between any two of them. In some embodiments, the mass ratio of the boron element in the boron compound to the total mass of the nano-silicon and graphite includes but is not limited to 0.01:1, 0.02:1, 0.03:1, 0.05:1, 0.06:1, 0.07:1, 0.08:1, 0.09:1, 0.1:1. The present invention adopts a boron compound with an appropriate dosage ratio, so that the obtained boron oxide can better adhere the nano-silicon to the graphite surface uniformly, and can improve the adhesion between the nano-silicon and the graphite.
[0063] In some embodiments, the mass ratio of the boron compound to water is 1:(30 - 40). The water includes deionized water, etc. In some embodiments, the mass ratio of the boron compound to water includes but is not limited to 1:30, 1:32, 1:33, 1:35, 1:38, 1:40, etc. The present invention adopts an appropriate dosage ratio of water to ensure the充分 mixing and uniformity of the materials, which is beneficial to subsequent operations and to ensure the performance of the matrix material.
[0064] In some embodiments, the mass ratio of the pyrolytic carbon source in the pyrolytic carbon source solution to the matrix material is (2 - 6):(1 - 5). The mass ratio of the pyrolytic carbon source to the matrix material is to ensure that the coating layer has an appropriate thickness and uniformity, so as to improve the electrochemical performance of the finally obtained silicon-carbon negative electrode material.
[0065] In some embodiments, the rotation speed of the first mixing is 1500 - 2000 rpm, including but not limited to 1500 rpm, 1600 rpm, 1700 rpm, 1800 rpm, 1850 rpm, 1900 rpm, 1950 rpm, 2000 rpm, etc., or the range value between any two of them; the time of the first mixing is 20 - 40 min, including but not limited to 20 min, 25 min, 30 min, 35 min, 40 min, etc., or the range value between any two of them. The present invention adopts an appropriate rotation speed and time for the first mixing, so as to ensure the充分 mixing of each material.
[0066] In some embodiments, the temperature of the first calcination is 300-600°C, including but not limited to 300°C, 350°C, 400°C, 500°C, 600°C, etc., or any range between the two; the time of the first calcination is 1-10h, including but not limited to 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, etc., or any range between the two. The first calcination is carried out under protective gas conditions, such as nitrogen, argon, helium, etc. The suitable first calcination conditions of the present invention are conducive to ensuring the bonding effect of the co-solvent and improving the electrochemical properties of the matrix material.
[0067] In some embodiments, a first drying is further included between the first mixing and the first calcination. The first drying is performed to remove moisture. The temperature of the first drying is 80 to 120°C, including but not limited to 80°C, 85°C, 90°C, 95°C, 100°C, 110°C, 120°C, or any range between the two; the time of the first drying is 24 to 48h, including but not limited to 24h, 25h, 30h, 35h, 40h, 45h or 48h, etc., or any range between the two.
[0068] In some embodiments, it also includes: performing a first crushing process and a first screening process on the material after the first roasting in sequence. Through the first crushing and the first screening, a matrix material of suitable particle size is obtained. In some embodiments, the rotation speed of the crushing process is 200-300rpm, including but not limited to 200rpm, 220rpm, 250rpm, 280rpm, 300rpm, etc., or any range value between the two. The time of the crushing process is 4-5h, including but not limited to 4h, 4.5h or 5h, etc. The first screening process includes: passing through a 350 mesh sieve.
[0069] In some embodiments, the second mixing speed is 1500-2000rpm, including but not limited to 1500rpm, 1600rpm, 1700rpm, 1800rpm, 1900rpm, 2000rpm, etc., or any range between the two. The second mixing time is 20-40min, including but not limited to 20min, 25min, 30min, 35min, 40min, etc., or any range between the two. The present invention fully mixes the matrix material and the pyrolytic carbon source through the second mixing under appropriate conditions.
[0070] In some embodiments, the temperature of the second calcination is 600-950°C, including but not limited to 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, etc., or any range between the two. The time of the second calcination is 1-10h, including but not limited to 1h, 2h, 3h, 5h, 6h, 8h or 10h, etc., or any range between the two. The second calcination is carried out under protective gas conditions, such as nitrogen, argon, etc. The present invention adopts suitable second calcination conditions to ensure the coating effect of the carbon coating layer.
[0071] In some embodiments, the second drying is further included between the second mixing and the second calcination. The temperature of the second drying is 80 to 120°C, including but not limited to 80°C, 90°C, 100°C, 110°C, 120°C, etc., or any range between the two. The time of the second drying is 24 to 48h, including but not limited to 24h, 30h, 35h, 40h, 45h, 48h, etc. The second drying is performed to remove moisture.
[0072] In some embodiments, it also includes: performing a second crushing process and a second screening process on the material obtained by the second calcination in sequence. A silicon-carbon composite material of suitable particle size is obtained by the second crushing process and the second screening process. In some embodiments, the rotation speed of the second crushing is 200-300rpm, including but not limited to 200rpm, 220rpm, 250rpm, 280rpm or 300rpm, etc., or any range value between the two. The time of the second crushing is 4-5h, including but not limited to 4h, 4.5h or 5h, etc., or any range value between the two. The second screening process includes: passing through a 350 mesh sieve.
[0073] In a preferred embodiment, the method for preparing the silicon-carbon negative electrode material comprises the following steps:
[0074] (a) performing a first mixing of graphite, nano-silicon, boron compound and water, wherein the speed of the first mixing is 1500-2000 rpm and the time of the first mixing is 20-40 min; performing a first drying of the first mixed material, wherein the temperature of the first drying is 80-120° C. and the time of the first drying is 24-48 h; performing a first roasting of the first dried material, wherein the first roasting is performed under protective gas conditions, the temperature of the first roasting is 300-600° C. and the time of the first roasting is 1-10 h; performing a first crushing treatment and a first screening treatment on the first roasted material in sequence; the speed of the first crushing treatment is 200-300 rpm and the time of the first crushing treatment is 4-5 h, and the first screening treatment includes: passing through a 350 mesh sieve to obtain a matrix material.
[0075] (b) performing a second mixing of the matrix material and the pyrolysis carbon source solution, the second mixing speed is 1500-2000rpm, and the second mixing time is 20-40min; performing a second drying of the second mixed material, the second drying temperature is 80-120°C, and the second drying time is 24-48h; performing a second roasting of the second dried material, the second roasting is carried out under protective gas conditions, the second roasting temperature is 600-950°C, and the second roasting time is 1-10h; performing a second crushing treatment and a second screening treatment on the material obtained by the second roasting in sequence, the second crushing speed is 200-300rpm, the second crushing time is 4-5h, and the second screening treatment includes: passing through a 350-mesh sieve to obtain a silicon-carbon negative electrode material.
[0076] The silicon-carbon negative electrode material of the present invention is as follows Figure 1 As shown, it includes a substrate 1 and a coating layer 2 coated on the surface of the substrate 1, the substrate 1 includes a core 101 and a composite layer 102 located on the surface of the core 101; the core 101 contains graphite; the composite layer 103 contains nano-silicon and boron oxide; the coating layer 2 contains nano-carbon.
[0077] According to another aspect of the present invention, the present invention also relates to a negative electrode sheet, comprising the above-mentioned silicon-carbon negative electrode material, or the silicon-carbon negative electrode material prepared by the above-mentioned method for preparing the silicon-carbon negative electrode material.
[0078] The negative electrode sheet of the present invention comprises a negative electrode current collector and a negative electrode layer located on the surface of the negative electrode current collector; the negative electrode material comprises the above-mentioned silicon-carbon negative electrode material.
[0079] According to another aspect of the present invention, the present invention also relates to a battery, comprising the above-mentioned negative electrode sheet.
[0080] The battery of the present invention has high initial efficiency and excellent cycle performance, rate performance and safety performance.
[0081] The battery of the present invention comprises the above-mentioned negative electrode sheet, positive electrode sheet, separator and electrolyte.
[0082] According to another aspect of the present invention, the present invention also relates to an electrical device comprising the above-mentioned battery.
[0083] The electrical equipment of the present invention includes electric vehicles, portable equipment and the like.
[0084] The following is further explained in conjunction with specific embodiments and comparative examples.
[0085] Example 1
[0086] This embodiment provides a method for preparing a silicon-carbon negative electrode material, comprising the following steps:
[0087] (1) 15 g of nano silicon powder, 85 g of graphite powder, 5 g of nano boric acid powder and 150 g of deionized water were added to a vertical mixer for first mixing at a speed of 1500 rpm for 20 min, followed by sieving (to separate the material from the grinding balls), placing the mixed material in a ceramic plate, and placing the ceramic plate in a forced air drying oven for first drying at a temperature of 80° C. for 24 h.
[0088] (2) The dried material is placed in a sagger, and placed in an atmosphere muffle furnace for a first calcination, with nitrogen introduced as a protective gas. After calcination at 550° C. for 1 h, the material is taken out and placed in a vertical mixer for a first crushing process.
[0089] (3) The material after the first crushing was passed through a 350 mesh sieve to obtain a matrix material, the matrix material was placed in a double planetary mixer, and a 5% PVDF solution was added at a mass ratio of 1:2 between the matrix material and PVDF, and then a second mixing was performed, the speed of the second mixing was 1500 rpm, and the time was 30 min. The slurry was placed in a ceramic dish and placed in a blast oven for a second drying at a temperature of 80° C. for 24 h.
[0090] (4) The material after the second drying is loaded into a sagger, placed in an atmosphere muffle furnace for a second calcination, nitrogen is introduced as a protective gas, carbonized at 800°C for 5 hours, taken out after cooling, and placed in a high-speed mixer for a second crushing treatment, mixed and crushed at a speed of 200 rpm for 30 minutes, taken out and sieved through a 350-mesh sieve to obtain a silicon-carbon composite material.
[0091] Example 2
[0092] This embodiment provides a method for preparing a silicon-carbon negative electrode material, comprising the following steps:
[0093] (1) 15 g of nano silicon powder, 85 g of graphite powder, 5 g of nano boric acid powder and 150 g of deionized water were added to a vertical mixer for first mixing. The speed of the first mixing was 1500 rpm and the mixing time was 30 min. The mixture was then sieved (to separate the material from the grinding balls). The obtained mixture was placed in a ceramic plate, and the ceramic plate was placed in a blast drying oven for first drying. The temperature of the first drying was 80° C. and the drying time was 24 h.
[0094] (2) The dried material is placed in a sagger, placed in an atmosphere muffle furnace for the first calcination, nitrogen is introduced as a protective gas, and the material is taken out after calcination at 550° C. for 2 h, and then placed in a vertical mixer for the first crushing.
[0095] (3) The material after the first crushing was passed through a 350 mesh sieve to obtain a matrix material, the matrix material was placed in a double planetary mixer, and a 5% PVDF solution was added at a mass ratio of 1:3 between the matrix material and PVDF, and then the first mixing was performed again at a speed of 2000 rpm for 30 minutes. The slurry was placed in a ceramic dish and placed in a blast oven for a second drying at a temperature of 80°C for 24 hours.
[0096] (4) The material after the second drying is loaded into a sagger, placed in an atmosphere muffle furnace for a second calcination, nitrogen is introduced as a protective gas, carbonized at 700°C for 5 hours, taken out after cooling, and placed in a high-speed mixer for a second crushing treatment, mixed and crushed at a speed of 250 rpm for 30 minutes, taken out and sieved through a 350-mesh sieve to obtain a silicon-carbon composite material.
[0097] Example 3
[0098] This embodiment provides a method for preparing a silicon-carbon negative electrode material, comprising the following steps:
[0099] (1) 15 g of nano silicon powder, 85 g of graphite powder, 5 g of nano boric acid powder and 150 g of deionized water were added into a vertical mixer for first mixing at a speed of 1500 rpm for 30 min, and then sieved (to separate the material and the grinding balls). The obtained mixture was placed into a ceramic plate, and the ceramic plate was placed into a forced air drying oven for first drying at a temperature of 80° C. for 48 h.
[0100] (2) The dried material is placed in a sagger, and placed in an atmosphere muffle furnace for a first calcination, with nitrogen introduced as a protective gas. After calcination at 550° C. for 2 h, the material is taken out and placed in a vertical mixer for a first crushing process.
[0101] (3) After the first crushing, the material was passed through a 350-mesh sieve to obtain a base material, which was placed in a double planetary mixer, and a starch solution after low-temperature gelatinization was added at a ratio of 5:6 between the base material and the starch, with the starch mass fraction in the starch solution being 6%, and then a second mixing was performed at a speed of 1800 rpm for 30 minutes. The slurry was placed in a ceramic dish and placed in a blast oven for a second drying at a temperature of 80° C. for 24 hours.
[0102] (4) The material after the second drying is loaded into a sagger, placed in an atmosphere muffle furnace for a second calcination, nitrogen is introduced as a protective gas, carbonized at 700°C for 5 hours, taken out after cooling, and placed in a high-speed mixer for a second crushing treatment, mixed and crushed at a speed of 300 rpm for 30 minutes, taken out and sieved through a 350-mesh sieve to obtain a silicon-carbon composite material.
[0103] Example 4
[0104] This embodiment provides a method for preparing a silicon-carbon negative electrode material, comprising the following steps:
[0105] (1) 15 g of nano silicon powder, 85 g of graphite powder, 5 g of nano boric acid powder and 150 g of deionized water were added to a vertical mixer for first mixing at a speed of 1500 rpm. After mixing for 30 min, the mixture was sieved and placed in a ceramic plate. The ceramic plate was placed in a forced air drying oven for first drying at a temperature of 80° C. for 24 h.
[0106] (2) The dried material is placed in a sagger, placed in an atmosphere muffle furnace for the first calcination, nitrogen is introduced as a protective gas, and the material is taken out after calcination at 550° C. for 2 h, and then placed in a vertical mixer for the first crushing.
[0107] (3) The material after the first crushing was passed through a 350 mesh sieve to obtain a base material, and the base material was placed in a double planetary mixer, and a starch solution after low-temperature gelatinization was added at a ratio of 5:4 of base material to starch, and the mass fraction of starch in the starch solution was 6%, and then a second mixing was performed at a speed of 2000 rpm and stirred for 30 minutes. The slurry was placed in a ceramic dish and placed in a blast oven for a second drying at a temperature of 80°C for 24 hours.
[0108] (4) The material after the second drying is loaded into a sagger, placed in an atmosphere muffle furnace for a second calcination, nitrogen is introduced as a protective gas, carbonized at 700°C for 5 hours, taken out after cooling, and placed in a high-speed mixer for a second crushing treatment, mixed and crushed at a speed of 300 rpm for 30 minutes, taken out and sieved through a 350-mesh sieve to obtain a silicon-carbon composite material.
[0109] Comparative Example 1
[0110] This comparative example provides a method for preparing a silicon-carbon negative electrode material, comprising the following steps:
[0111] 15g of nano silicon powder and 85g of graphite powder were mixed in a mixer at 1500rpm for 20min to obtain a premixed material, and then 5% PVDF solution was added according to the mass ratio of material to PVDF of 1:2, and mixed and stirred for 30min. The obtained slurry was placed in a ceramic dish and dried in a blast oven at 80°C for 24h. The dried material was loaded into a sagger, placed in an atmosphere muffle furnace, nitrogen was introduced as a protective gas, carbonized at 800°C for 5h, taken out after cooling, put into a high-speed mixer, mixed and crushed at 200rpm for 30min, and then taken out and sieved through a 350-mesh sieve to obtain a silicon-carbon composite material.
[0112] Experimental example
[0113] The silicon-carbon negative electrode materials obtained in each embodiment and comparative example were respectively prepared into batteries, specifically including: mixing each material with solvent NMP according to the ratio of silicon-carbon negative electrode material: SuperP: PVDF of 8:1:1 to obtain negative electrode slurry, coating the negative electrode slurry on copper foil, and obtaining negative electrode sheet after drying; using metallic lithium as the counter electrode; using 1 mol / L LiPF6 solution as electrolyte, using EC, DEC and DMC as solvents, and the volume ratio of EC, DEC and DMC is 1:1:1; making 2032 button batteries and conducting electrochemical performance tests. Test conditions: 25°C, 0.1C, 0.05-2.5V.
[0114] The battery chemical performance test results are shown in Table 1.
[0115] Table 1 Electrochemical performance test results of the battery
[0116]
[0117]
[0118] It can be seen from Table 1 above that the battery further prepared by the silicon-carbon negative electrode material obtained by the method of each embodiment of the present invention has excellent first discharge specific capacity and first coulombic efficiency, with the first discharge specific capacity being 440 mAh / g and the first coulombic efficiency being 79% and above.
[0119] The first coulombic efficiency of the battery further prepared by the silicon-carbon negative electrode material obtained by the methods of Comparative Examples 1 to 3 is relatively poor.
[0120] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A silicon-carbon negative electrode material, It is characterized in that It comprises a substrate and a coating layer coated on the surface of the substrate, wherein the substrate comprises an inner core and a composite layer located on the surface of the inner core; The inner core comprises graphite; The composite layer comprises nano-silicon and boron oxide; The coating layer contains nanocarbon.
2. The silicon-carbon negative electrode material according to claim 1, It is characterized in that The graphite includes spherical graphite.
3. The silicon-carbon negative electrode material according to claim 1, It is characterized in that The battery prepared by the silicon-carbon negative electrode material has a first discharge specific capacity of more than 440 mAh / g under the test conditions of 25°C, 0.1C, 0.05-2.5V; The first coulombic efficiency of the battery prepared by the silicon-carbon negative electrode material is 79% or above.
4. The method for preparing the silicon-carbon negative electrode material according to any one of claims 1 to 3, It is characterized in that The following steps are involved: Graphite, nano-silicon, boron compound and water are first mixed and first calcined to obtain a base material; the base material and a pyrolysis carbon source solution are second mixed and second calcined to obtain a silicon-carbon negative electrode material.
5. The method for preparing the silicon-carbon negative electrode material according to claim 4, It is characterized in that The invention comprises at least one of the following features (1) to (6): (1) The boron compound comprises at least one of boron oxide and boric acid; (2) The pyrolytic carbon source solution comprises a pyrolytic carbon source and water, wherein the pyrolytic carbon source accounts for 5% to 8% by mass of the pyrolytic carbon source solution; the pyrolytic carbon source comprises a water-soluble carbon source and / or a water-insoluble carbon source; (3) The mass ratio of the nano-silicon to the graphite is x:(1-x), wherein 0 <x≤0.4; (4) The ratio of the mass of the boron element in the boron compound to the total mass of the nano-silicon and graphite is y:1, wherein 0 <y≤0.1; (5) The mass ratio of the boron compound to the water is 1:(30-40); (6) The mass ratio of the pyrolytic carbon source in the pyrolytic carbon source solution to the matrix material is (2-6):(1-5).
6. The method for preparing the silicon-carbon negative electrode material according to claim 4, It is characterized in that Contains at least one of the following features (1) to (3): (1) The first mixing speed is 1500-2000 rpm, and the first mixing time is 20-40 min; (2) The temperature of the first calcination is 300 to 600° C., and the time of the first calcination is 1 to 10 hours; (3) The first calcination is carried out under protective gas conditions.
7. The method for preparing the silicon-carbon negative electrode material according to claim 4, It is characterized in that Contains at least one of the following features (1) to (5): (1) A first drying step is included between the first mixing and the first calcining; (2) The temperature of the first drying is 80 to 120° C., and the time of the first drying is 24 to 48 hours; (3) further comprising: sequentially performing a first crushing process and a first screening process on the first calcined material; (4) The rotation speed of the first crushing process is 200 to 300 rpm, and the time of the first crushing process is 4 to 5 hours; (5) The first screening process includes: passing through a 350-mesh sieve.
8. The method for preparing the silicon-carbon negative electrode material according to claim 4, It is characterized in that Contains at least one of the following features (1) to (3): (1) The speed of the second mixing is 1500-2000 rpm, and the time of the second mixing is 20-40 min; (2) The temperature of the second calcination is 600 to 950° C., and the time of the second calcination is 1 to 10 hours; (3) The second calcination is carried out under protective gas conditions.
9. The method for preparing the silicon-carbon negative electrode material according to claim 4, It is characterized in that Contains at least one of the following features (1) to (5): (1) a second drying step is included between the second mixing and the second calcining; (2) The temperature of the second drying is 80 to 120° C., and the time of the second drying is 24 to 48 hours; (3) further comprising: sequentially performing a second crushing process and a second screening process on the material obtained by the second roasting; (4) The rotation speed of the second crushing is 200-300 rpm, and the time of the second crushing is 4-5 hours; (5) The second screening process includes: passing through a 350-mesh sieve.
10. A negative electrode sheet, It is characterized in that The invention comprises the silicon-carbon negative electrode material according to any one of claims 1 to 3, or the silicon-carbon negative electrode material prepared by the method for preparing the silicon-carbon negative electrode material according to any one of claims 4 to 9.
11. A battery, It is characterized in that Includes the negative electrode sheet as claimed in claim 10.
12. An electrical device, It is characterized in that Comprising the battery of claim 11.
Citation Information
Cited By
Silicon-carbon negative electrode material, and preparation method therefor and use thereof
WO2026031809A1
